2021
DOI: 10.1109/access.2021.3055729
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Split-Type Pressure Sensor for High-Temperature Applications

Abstract: This study proposes a split-type pressure sensor based on differential capacitance that can be applied to in-situ accurate pressure testing in high-temperature environments. The sensor is mainly composed of a high-temperature resistant chip and a high-temperature resistant encapsulation structure. The chip is made of a ceramic substrate and presents a differential capacitance structure that can withstand high temperatures and effectively restrain the temperature drift. The encapsulation presents a split-type s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Moreover, they are generally limited by the leakage currents at the insulating pn-junctions, which increase with the increasing temperature, so that the maximum operating temperature of a silicon pressure sensor or force sensor is usually around 125 • C [24]. With the use of silicon-on-insulator (SOI) and silicon carbide (SiC), pressure sensors with a temperature range up to about 350 • C can be realized, but with much higher costs and more complex fabrication processes [25]. Peng et al demonstrated in [26] an elaborate process for the fabrication of piezoresistive pressure sensor by using SOI.…”
Section: Piezoresistive Sensorsmentioning
confidence: 99%
“…Moreover, they are generally limited by the leakage currents at the insulating pn-junctions, which increase with the increasing temperature, so that the maximum operating temperature of a silicon pressure sensor or force sensor is usually around 125 • C [24]. With the use of silicon-on-insulator (SOI) and silicon carbide (SiC), pressure sensors with a temperature range up to about 350 • C can be realized, but with much higher costs and more complex fabrication processes [25]. Peng et al demonstrated in [26] an elaborate process for the fabrication of piezoresistive pressure sensor by using SOI.…”
Section: Piezoresistive Sensorsmentioning
confidence: 99%
“…Capacitive pressure sensors have high resolution and low thermal sensitivity drift [ 11 , 12 ] and can also be miniaturized at low cost. For example, Chen Li reported a split-type pressure sensor based on differential capability with a working temperature range of 25–400 °C and a sensitivity of 9.27 mV/kPa [ 13 , 14 ]. However, capacitive pressure sensors can be affected by parasitic capacitance creating difficulties ensuring measurement accuracy in complex environments.…”
Section: Introductionmentioning
confidence: 99%